The challenges measuring the effectiveness of a statewide Medicaid long-term care managed care programme: the Florida experience. (1st January 2012) - Golden, Adam G.; Roos, Bernard A.; Silverman, Michael A.; Wan, Thomas T.H.
Recent passage of legislation in Florida mandating the development of a statewide Medicaid managed care long-term care plan was initiated to facilitate the utilisation of home- and community-based long-term care services in place of high cost, non-skilled nursing home care. However, programme savings will be limited if the care needs of nursing home residents exceed that currently provided by community-based programmes. This article reports on the challenges that arose from our efforts to compare the care burden of nursing home residents and nursing home-eligible Medicaid waiver programme enrolees. Our experience will better enable policy researchers and managed care plans to design comparative effective studies that address the rebalancing of long-term care resources.